Kinetika Adsorpsi Zat Warna Metilen Blue Menggunakan Silika Xerogel dari Abu Terbang (Fly Ash) - Annisa Haqqu; Edi Nasra; Desy Kurniawati (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
Coal is an organic mineral from ancient plant remains that settles and goes through physical or chemical processes over a period of up to millions of years. Coal is used as a source of steam-powered electrical energy through combustion which produces fly ash waste. fly ash contains various chemical materials such as SiO2; Al2O3; Fe2O3. The potential chemical content makes fly ash which can be used as an adsorbent for heavy metals and dyes by forming silica xerogel. To increase the silica oxide content in fly ash, a washing process is carried out with various solvents. Research on the adsorption of methylene blue dye using silica xerogel from fly ash with variations in contact time. The results showed that silica xerogel from fly ash was able to adsorb methylene blue dye at a contact time of 90 minutes. Adsorption kinetics follows a pseudo second order model with an R2 value that is better than pseudo first order. It can be seen that the R2 value respectively shows a linear regression of 0.703 for pseudo first order and 1 for pseudo second order.